2021
DOI: 10.1007/s11676-021-01360-6
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput phenotyping of two plant-size traits of Eucalyptus species using neural networks

Abstract: In forest modeling to estimate the volume of wood, artificial intelligence has been shown to be quite efficient, especially using artificial neural networks (ANNs). Here we tested whether diameter at breast height (DBH) and the total plant height (Ht) of eucalyptus can be predicted at the stand level using spectral bands measured by an unmanned aerial vehicle (UAV) multispectral sensor and vegetation indices. To do so, using the data obtained by the UAV as input variables, we tested different configurations (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Some other VIs that can be associated with the presence of pathogens are related to water content in plants and chlorophyll pigmentation. The Triangle Vegetation Index (TVI) [ 66 ] that determines the radiant energy absorption of chlorophyll has been used to classify healthy and unhealthy crops. NDRE is calculated similarly to the NDVI, but uses a red edge instead of the red band [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some other VIs that can be associated with the presence of pathogens are related to water content in plants and chlorophyll pigmentation. The Triangle Vegetation Index (TVI) [ 66 ] that determines the radiant energy absorption of chlorophyll has been used to classify healthy and unhealthy crops. NDRE is calculated similarly to the NDVI, but uses a red edge instead of the red band [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…Individual tree segmentation and species identification are possible from both drone-based imagery and drone-based Light Detection and Ranging (LiDAR) [317][318][319]. Near-infrared (NIR), wide-infrared, and RGB sensors can be used to effectively measure tree water stress via various indices, such as the Normalized Difference Vegetation Index (NDVI) [320,321]. With the aid of machine-learning algorithms, both hyperspectral imagery and LiDAR accurately estimate tree height and Diameter at Breast Height (DBH) [321][322][323].…”
Section: Phenomics Field Scale Technologies For Oak Researchmentioning
confidence: 99%
“…ANNs are computational models inspired by the human brain, whose learning and generalization capabilities make them capable of solving complex problems, such as cultivar classification studies using imaging processing in different crops [14]. Studies have demonstrated that the ANN and RF algorithms used to process spectral data can also be used to estimate the diameter at breast height and total height of eucalyptus trees, making this a promising approach contributing to the inventory and management of planted forests [15,16]. Ref.…”
Section: Introductionmentioning
confidence: 99%